2007
DOI: 10.1007/s12039-007-0063-z
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of redox species in condensed phase

Abstract: We give a detailed description of the use of explicit as well as implicit solvation treatments to compute the reduction potentials of biomolecules in a medium. The explicit solvent method involves quantum mechanical/molecular mechanics (QM/MM) treatment of the solvated moiety followed by a Monte-Carlo (MC) simulation of the primary solvent layer. The QM task for considerably large biomolecules is normally carried out by density functional treatment (DFT) along with the MM-assisted evaluation of the most stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…As a matter of fact, PCM does not explicitly consider any fluctuation effect from the average solvent polarization. 24 For all three diradical pairs PCM optimization calculations have been carried out taking blood plasma (e = 58) as the medium. With the PCM optimized geometry of these diradicals in a high spin state, the BS treatment has been performed to ascertain the magnetic nature of these molecules in blood plasma.…”
Section: Theoretical Background and Methodologymentioning
confidence: 99%
“…As a matter of fact, PCM does not explicitly consider any fluctuation effect from the average solvent polarization. 24 For all three diradical pairs PCM optimization calculations have been carried out taking blood plasma (e = 58) as the medium. With the PCM optimized geometry of these diradicals in a high spin state, the BS treatment has been performed to ascertain the magnetic nature of these molecules in blood plasma.…”
Section: Theoretical Background and Methodologymentioning
confidence: 99%
“…450 The authors demonstrated that the method could be an efficient approach to free energy simulations of complex electron transfer reactions. 450 Several other enzymatic redox reactions have also been studied recently using the tools of computational electrochemistry, in particular for the following enzymes: photosystem II, 270,[451][452][453] ribonuclease reductase, 454,455 rubredoxin, 456 green fluorescent protein, 457,458 adenosine-5 0 -phosphosulfate reductase, 459 methyltransferases, 460 monoamine oxidase B, 461 and methionine synthase. 462 Billiet et al 463 have studied the thermodynamics of thiol sulfenylation in the sulfenic acid-forming protein human Prx.…”
Section: Applicationsmentioning
confidence: 99%